CARBON STOCK AND DYNAMICS IN NATURAL REGENERATION IN MANAGED FOREST IN THE CENTRAL AMAZON - Luna, Elifran Roque; Freitas, Filipe Campos de; Azevedo, Celso Paulo de; Souza, Cintia Rodrigues de (Floresta, 2024)
Around 2% of the living biomass above ground is found in the natural regeneration of tree species. Despite being a relatively low value, diagnosing the lower stratum of the forest is important in the current context of climate change. The aim of this study was to evaluate the effects of forest management on the carbon stock and dynamics of natural regeneration 20 years after logging in a forest in the Central Amazon. Data collection was carried out in three Annual Production Units (APU) that received exploration in the years 1996, 1997 and 1998. Data from continuous forest inventories carried out in 41 sampling units were used, with four measurement periods: a pre-exploratory and three other post-forest exploration. The carbon stock was estimated in trees with a diameter at breast height between 5 and 15 cm and the Annual Periodic Increment in carbon (APIc) and the carbon entry and mortality rates were calculated. The carbon stock ranged from 10.80 ± 1.27 Mg ha-1 to 14.86 ± 0.81 Mg ha-1. The APIc ranged from 0.18 ± 0.03 Mg ha-1 year-1 to 0.59 ± 0.25 Mg ha-1 year-1, with an entry rate of 0.00% to 3.26% and mortality between 3.35% and 13.84%. The carbon stock and APIc were not significantly influenced by the forestry management applied to the forest, with only time as a determining factor in its dynamics. Considering natural regeneration, it is concluded that the managed forest is capable of recovering the carbon stock lost during the forest management process.